Adaptive Reuse: The Cases of Kathmandu Valley - Shrestha, Kushan Kumar; Piyush,; Shrestha, Saubhagya; Bahadur Gurung, Som; Singh Dongol, Moon (KEC Journal of Science and Engineering, 2026)
In the time of environment urgency and cultural loss, adaptive reuse has emerged as an important sustainable architecture. This research explores how innovative materials and design techniques supports adaptive reuse that not only addresses ecological concerns but also respects and preserves the historical and cultural identity focusing on adaptive reuse in Kathmandu valley. The study evaluates adaptive reuse in two cases: Hotel Shanker and Babar Mahal Revisited. Through these case studies, it examines how context specific materials and design strategies have been applied and what outcomes they produced. Overall, it was found that constructing a new building of similar size would use 2.15 to 3 times more embodied energy and emit 2.62 to 3.7 times more carbon.